MODEL AKULTURASI SCHUMANN DALAM BUKU ARABIYAH BAINA YADAIK SEBAGAI PENGEMBANGAN BI’AH LUGHAWIYAH PONDOK AL-ISHLAH LAMONGAN - Al-Furqaan, Dimas Luqman; Sudesi, Abdul Rohman (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
In developing bi'ah lughawiyah, which has been running since its inception, Al-Ishlah Islamic Boarding School Lamongan applied the Baina Yadaik Arabiyah textbook. This step was taken so the students could acculturate to the Arab-Islamic culture as contained in Baina Yadaik's Arabiyah book. So, this study aims to analyze Schumann's acculturation model in the Arabic book by Baina Yadaik for the development of bi'ah lughawiyah PP Al-Ishlah Lamongan. The methodology uses a descriptive qualitative research type based on Schumann's perspective. In addition, this study uses a literary approach with primary data sources in the form of Schumann's culturalization model in the book Al-Arabiyah Baina Yadaik. The results and discussion in this study include: 1) the acculturation model includes social variables, namely cultural domination, the pattern of integration, level of exposure to two language groups, level of cohesiveness of the second language learning group, size of the second language study group, level of conformity, and evaluation of attitudes between groups and also psychological variables including language shock, culture shock, ego permeability, motivation; 2) All aspects of cultural competency in Baina Yadaik's Arabiyah book which were developed in bi'ah lughawiyah PP Al-Ishlah Lamongan are in line with the social and psychological variables of the acculturation model from Schumann's perspective.